Innovating a Telecollaboration Programme to Prepare Learners with 21st Century Skills: A Case Study - Leviana Vinanda (Indonesia Technology-Enhanced Language Learning (iTELL) Journal, 2024)
This paper discussed the ways a telecollaboration programme can be innovated as a learning model that integrates technology into language learning to enrich the learners’ 21st century skills. These skills include competencies to communicate and collaborate with multilingual and multicultural speakers and criticality as a part of global citizen education. Pedagogical lingua franca and task-based language teaching were opted to provide principles for innovating the telecollaboration programme. The study was carried out in a general English class for adolescent learners in Indonesia in partnership with a foreign language school in Russia. The findings indicated the importance of enabling multimodality on digital platforms alongside well-defined and well-structured task design when creating a telecollaboration programme. The teacher’s roles as a programme designer, learning facilitator, and mentor, and finally as a researcher who utilised stages in action research and an insider perspective to reflect on the creation and implementation process of the telecollaboration programme, were also elaborated.